Hydrogen Cyanamide Induced Cutaneous Reactions: Occupational Pesticide Poisoning and Need for Surveillance - Inamdar, S Z; J, Chandrhas; CH, Srinath; V Kulkarni, Raghavendra (Indian Journal of Pharmacy Practice)
Pesticides are used widely throughout the world and is one of major cause of occupational, accidental and intentional poisoning with an estimated 3 million cases annually with reported 2,20,000 deaths worldwide. On an average 3% of agricultural workers in developing countries suffer an episode of pesticide poisoning per year. An 18 year old male patient with cutaneous reactions admitted to the medicine ward revealed to the exposure and use of pesticide (Dormex) in the agricultural field. The poison was investigated for the observed cuteneous reaction and the detailed poison information was provided. The patient was diagnosis with irritant contact dermatitis with secondary infection due to exposure to Dormex. The patient was effectively treated with corticosteroids and antihistamines. Dormex is a plant growth regulator with Hydrogen Cyanamide as an active ingredient. Hydrogen cyanamide is known to cause severe cutaneous reactions such as erythema multiform (EM), Stevens Johnsons Syndrome (SJS), Toxic Epidermal Necrolysis (TEN). Lack of awareness of its adverse effects and improper handling pose the risk of toxicity which can be prevented by taking appropriate precautionary measures against the exposure.
Keywords: Dormex; Erythema multiform; Hydrogen Cyanamide; Pesticide